2014
DOI: 10.1371/journal.pone.0089378
|View full text |Cite
|
Sign up to set email alerts
|

Do the Ticks of Birds at an Important Migratory Hotspot Reflect the Seasonal Dynamics of Ixodes ricinus at the Migration Initiation Site? A Case Study in the Danube Delta

Abstract: Migratory birds play important roles as distributors of ticks within and between continents. In the Old World, the most important migratory route of birds links Asia, Europe and Africa. During their migration, birds use various stopover sites, where they feed and rest and where ticks may attach or detach, creating new natural foci for vector-borne diseases. Danube Delta is one of the most important migration hotspots and so far no studies were focused on ticks of migratory birds herein. The aim of the present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
39
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 43 publications
4
39
0
6
Order By: Relevance
“…The total prevalence of tick infestation from 2011 to 2012 at Wicie ringing station, Poland, was 40.7% in spring and 40.0% in autumn. Similar levels of infestation have been recorded in other Western and Eastern bird migration routes in Europe (Nuorteva and Hoogstraal 1963;Hoogstraal et al 1964;Kahl 1971;Kaiser et al 1974;Walter et al 1979;Osacar-Jimenez et al 1998;Comstedt et al 2006;Mikula et al 2011;Nowak-Chmura et al 2012;Movila et al 2013;Sándor et al 2014;Ciebiera et al 2014). The tick prevalence on migratory birds on the Polish Baltic coast has increased from 31% in spring and 22% in autumn since 1981 (Nowak-Chmura et al 2012).…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The total prevalence of tick infestation from 2011 to 2012 at Wicie ringing station, Poland, was 40.7% in spring and 40.0% in autumn. Similar levels of infestation have been recorded in other Western and Eastern bird migration routes in Europe (Nuorteva and Hoogstraal 1963;Hoogstraal et al 1964;Kahl 1971;Kaiser et al 1974;Walter et al 1979;Osacar-Jimenez et al 1998;Comstedt et al 2006;Mikula et al 2011;Nowak-Chmura et al 2012;Movila et al 2013;Sándor et al 2014;Ciebiera et al 2014). The tick prevalence on migratory birds on the Polish Baltic coast has increased from 31% in spring and 22% in autumn since 1981 (Nowak-Chmura et al 2012).…”
Section: Discussionsupporting
confidence: 70%
“…were found on birds during migration (Hornok et al 2014a, b). In the Danube Delta I. ricinus was dominant, however I. arboricola, I. redikorzevi and H. punctata also occurred (Sándor et al 2014), in Greece I. frontalis, I. acuminatus, H. aegyptium and H. marginatum were recorded (Diakou et al 2016). In Egypt and Cyprus detailed research by Nuorteva and Hoogstraal (1963), Hoogstraal et al (1963Hoogstraal et al ( , 1964, Kaiser et al (1974) indicated that birds are able to transport at least 13 ticks species H. rufipes, A.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Such a geographical delimitation may result from higher humidity (Gray et al, 2013) as well as the ecological diversity of the habitats (Mihalca et al, 2012;Sándor et al, 2014). These qualities, collectively, represent more suitable conditions for the ticks.…”
Section: Discussionmentioning
confidence: 99%
“…As one of Europe's largest wetlands, the Danube Delta Biosphere Reserve (DDBR) located in the southeast of Romania, is a very biodiverse and heterogeneous complex of ecosystems [10]. The region is a major hub for bird migration along main African-Eurasian fly corridors, with ecoclimatic conditions suitable for abundant and diverse populations of arthropod vectors [11][12][13][14], which may allow pathogen import and maintenance [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%